Hubungan Prenatal Yoga Terhadap Kecemasan Ibu Hamil Trimester III Di TPMB Tri Imawati S.ST., Bdn Kota Metro - Fadilah, Intan; Kurniasari, Devi; Zarma, Zarma (Universitas Malahayati Bandar Lampung, 2025)
Anxiety in pregnant women in the third trimester is a psychological problem that often occurs before childbirth. High levels of anxiety can have a negative impact on the condition of the mother and fetus. Prenatal yoga is a non-pharmacological intervention that has been proven effective in reducing anxiety during pregnancy.This study aims to determine the relationship between prenatal yoga and anxiety levels in pregnant women in their third trimester at TPMB Tri Imawati SST., Bdn Metro City. This study uses a quantitative approach with a cross-sectional design. The sample consisted of 20 pregnant women in their third trimester who were selected using accidental sampling. Data were collected using the Prenatal Anxiety Screening Scale (PASS) questionnaire and analyzed using the Chi-Square test.The results showed that of the 10 pregnant women who participated in prenatal yoga, the majority experienced mild anxiety and none experienced anxiety. In contrast, of the 10 pregnant women who did not participate in prenatal yoga, all experienced severe anxiety. The analysis results showed a significant relationship between prenatal yoga and anxiety levels (p < 0.05).There is a significant relationship between prenatal yoga and anxiety levels in pregnant women in their third trimester. Prenatal yoga can be used as an alternative intervention to reduce anxiety before childbirth. Keywords: Prenatal yoga, anxiety, pregnant women, third trimester ABSTRAK Kecemasan pada ibu hamil trimester III merupakan permasalahan psikologis yang sering terjadi menjelang persalinan. Tingkat kecemasan yang tinggi dapat berdampak buruk terhadap kondisi ibu dan janin. Prenatal yoga merupakan intervensi non- farmakologis yang terbukti efektif dalam mengurangi kecemasan selama kehamilan.Penelitian ini bertujuan untuk mengetahui hubungan antara prenatal yoga terhadap tingkat kecemasan pada ibu hamil trimester III di TPMB Tri Imawati SST., Bdn Kota Metro. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross- sectional. Sampel terdiri dari 20 ibu hamil trimester III yang dipilih menggunakan teknik accidental sampling. Data dikumpulkan menggunakan kuesioner Prenatal Anxiety Screening Scale (PASS) dan dianalisis dengan uji Chi-Square.Hasil penelitian menunjukkan bahwa dari 10 ibu hamil yang mengikuti prenatal yoga, mayoritas mengalami kecemasan ringan dan tidak ada kecemasan. Sebaliknya, dari 10 ibu hamil yang tidak mengikuti prenatal yoga, seluruhnya mengalami kecemasan berat. Hasil analisis menunjukkan adanya hubungan yang signifikan antara prenatal yoga dengan tingkat kecemasan (p < 0,05).Terdapat hubungan yang signifikan antara prenatal yoga dengan tingkat kecemasan pada ibu hamil trimester III. Prenatal yoga dapat dijadikan sebagai alternatif intervensi dalam menurunkan kecemasan menjelang persalinan Kata Kunci: Prenatal yoga, kecemasan, ibu hamil, trimester III